2016
DOI: 10.1111/ipd.12278
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy for localized juvenile spongiotic gingival hyperplasia: preliminary findings on two cases

Abstract: Cryotherapy appears to be successfully in LJSGH and well received by paediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 8 publications
1
32
0
2
Order By: Relevance
“…After clinical and/or histopathologic diagnosis, there is no specific treatment for LJSGH except surgery . Although it has been suggested that many cases of LJSGH undergo spontaneous resolution, no prospective study has been carried out to confirm this hypothesis . Nor have spontaneously resolving cases been reported in the 10‐year interval since the lesion's first description.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After clinical and/or histopathologic diagnosis, there is no specific treatment for LJSGH except surgery . Although it has been suggested that many cases of LJSGH undergo spontaneous resolution, no prospective study has been carried out to confirm this hypothesis . Nor have spontaneously resolving cases been reported in the 10‐year interval since the lesion's first description.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of localized cases in the literature have been treated by surgical excision with a significant recurrence rate (6% to 16%) . There have been no consistent correlations with exclusive factors of each patient to suggest a reason for the recurrence .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When nitrous oxide is released from high pressure inside the cryoprobe to the lower pressure cryotip, the drop in temperature allows freezing of the tissues to occur (6,10). Current protocols suggest for most benign mucosal lesions a 1-2 minute freeze/thaw cycle, for premalignant/malignant lesions three 2 minute freeze/thaw cycles and for smaller lesions, shorter freeze cycles (20-30 seconds) using a cryoprobe are adequate (6,10).…”
Section: Discussionmentioning
confidence: 99%